Os Direitos humanos entre polícia e política - DELUCHEY, Jean-François Yves (Universidade Federal do Pará, 2018)
Based on analysis of the 1948 UN Universal Declaration of Human Rights, and on the differentiation between the concepts of police and politics by the French philosopher Jacques Rancière, The author identifies that there is currently a police approach (or governmental) of human rights. The author criticizes the scam of this approach and recommends a repolitization of the human rights matters in order to seek the renewal of their universal dimension.